If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0x + 2y + 2z = 0 Anything times zero is zero. 0x + 2y + 2z = 0 Remove the zero: 2y + 2z = 0 Solving 2y + 2z = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2z' to each side of the equation. 2y + 2z + -2z = 0 + -2z Combine like terms: 2z + -2z = 0 2y + 0 = 0 + -2z 2y = 0 + -2z Remove the zero: 2y = -2z Divide each side by '2'. y = -1z Simplifying y = -1z
| -2x+x-5=3x+3 | | k(x)=3(x-1)(x+1) | | 1.06(1.26)(7-x)=8 | | -3r+7-7=13-7 | | 1.06(1.26)77-x=8 | | (2x^2)+2+14x=90 | | y=2+13y | | 20x+y=180 | | 12x+6x^2=9x^2 | | 2(5x+3)=x+6(x+1) | | 7y+3x=58 | | -3/7(2)-2=y | | 7+63y= | | 6p-8p+-5=-17 | | 55m+5= | | 7x+4+5x+3+2+5=180 | | .80(5-20x)=-44 | | (-3)^5/(-3)^8 | | 102=-3(6n-4) | | h(x)=(2x+5)(3x-1) | | 7^5/7^3 | | (-4)^8/(-4)^4 | | 8^4/8^0 | | -6x^2+11-13=0 | | (-3)^6/(-3)^8 | | (-8w+8)-(w-2)= | | 8cosx=6 | | -6w-(-4z+5w)+7z= | | 78x+31=90 | | 78x+31=180 | | y=-1+28x-171 | | (-2-n)+(6n-7)= |